Perception of service quality: A view from the perspective of the health sector (Encuentros, 2020)
The perception of the quality of the health service is considered an essential determinant for service satisfaction and behavioral intentions. Therefore, the objective of this study was to know the perception of the quality of public and private health service from the perspective of users in the context of a city in central-southern Chile. The methodology was carried out with 247 surveys. The data were analyzed descriptively and empirically using non-linear modeling. The results indicate that the elements of service quality in the health sector have an impact on the satisfaction of the service (using the proxy of whether or not it meets the requirements). Moreover, there are differences in perceptions of this quality in the public and private sectors, which vary if the frequency of use of health centers increases or decreases. These results hope to encourage health service providers to achieve an improvement in the quality of service provided considering the concerns and priorities of the stakeholders. The limitations of the study focus on the sample. Future research should expand the sample size and the adaptation of quantitative and qualitative empirical methods that favor a better understanding of the quality of the health service.